Exchange Relations for Finite Type Cluster Algebras with Acyclic Initial Seed and Principal Coefficients - Stella, S.; Tumarkin, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We give an explicit description of all the exchange relations in any finite type cluster algebra with acyclic initial seed and principal coefficients.